AB0846-HPR Independence in daily life activities in patients with rheumatoid arthritis and correlation with personal causation, disease activity and functionality. (23rd January 2014) - Urbina, A.; Beltran, D.; Sandoval, C.; Villarreal, L.; Real, A. P.; Boon, P.; Palomino, A.; Santos-Moreno, P.
Abstract : Background: Independence in daily life activities (DLA) is the capability to perform every procedure in adequate time and without any help. In rheumatoid arthritis (RA) patients functionality is reduced and usually they need others help to perform every day activities. This affects their desire to do things what is called personal causation. In RA patients these activities might be altered also by multiple causes as functional deterioration, psychological and social problems. There is no data about this field in RA patients. Objectives: The aim of this study was to describe level of independence in DLA in a RA patient's cohort and its relationship with disease activity, functionality and personal causation in a specialized center in Colombia. Methods: A descriptive cross sectional study was realized. A revision of medical records of a cohort of RA patients in a specialized center was performed, including occupational therapy records. All patients were evaluated for DAS28, HAQ, OPHI2 (Occupational Performance History Interview 2) and "Rodriguez y Arango" scale. Independence was classified in: Independent, semi-independent, semi-dependent and dependent in relation with the speed and the need of external help required for performance. Personal causation was classified in good and poor. Descriptive epidemiology was done, percentages and averages were calculated; and Kruskall-Wallis's statistics was used for by-variated analysis. Correlations were made for different levels of independence with DAS28, HAQ and poor personal causation. Results: Of the 177 RA patients included, 30 (16.9%) were men and 147 (83.1%) women. Mean age 59.6 y/o, for women 58.6 and for men 60.6. Average DAS 28 for all patients 3.04 and average HAQ were 0.35. Good personal causation was found in 45.7% of patients and poor in 54.3%. Regarding occupation of patients were: administrative workers (19.2%), housekeepers (19.2%), high impact workers (14.1%) and low impact workers (44.1%). According to independence level (percentage, average DAS28, average HAQ, poor personal causation percentage) patients were: dependent (no patients), semi-dependent 24 (5.1%, 3.57, 1.25, and 100%), semi-independent (61.1%, 2.97, 0.29, and 50.9%), independent (33.9%, 2.41, 0.18, and 28.3%). It was established a correlation between level of DLA and DAS28 (p < 0.0001), HAQ (p < 0.0002); also between disease activity and poor personal causation (p < 0.0094). Conclusions: Most patients were semi-independent, that is to say that most patients perform DLA with reduced speed but without help. Patients with higher levels of dependence showed higher disease activity and poorer functionality. Patients with poor personal causation had the most active disease (moderate by DAS28) and showed worst functionality. Disclosure of Interest: None Declared